Effect of beetroot or beetroot plus vitamin C supplementation on cardiovascular function in patients with coronary artery disease: protocol for a double-blind, placebo-controlled, randomised trial - Hamed Tabesh; Mohsen Nematy; Leila Sadat Bahrami; Mohsen Mohebaty; Seyyed Mostafa Arabi; Reza Rezvani (BMJ Open)
Introduction Coronary artery disease (CAD), classified into the atherosclerosis category, is a prevalent cardiovascular disease worldwide that is associated with serious comorbidities and death. The purpose of this study was to evaluate the effect of beetroot/beetroot plus vitamin C on cardiovascular health status and function in patients with CAD.Method and analysis A randomised, placebo-controlled, double-blind clinical trial to recruit 90 patients with CAD at the cardiac outpatient clinic and Imam Reza Hospital, Mashhad, Iran. Participants will be divided into three groups: (1) Those who receive 500 mg three times a day of beetroot capsules, (2) Those who receive 500 mg three times a day of beetroot plus vitamin C capsules, and (3) Those who receive placebo capsules three times a day for 4 weeks. Pulse wave velocity, Augmentation Index, heart rate, volume of oxygen (VO2) max/VO2 peak, peak heart rate, blood pressure, interleukin 6 (IL-6), high sensitivity C reactive protein, intercellular adhesion molecule, vascular cell adhesion molecule, lipid profile and anthropometry will be measured at the beginning and end of the intervention.Ethics and dissemination This study was approved by the Ethics Committee of Mashhad University of Medical Sciences (IR.MUMS.MEDICAL.REC.1399.717). All participants will be asked to complete the consent form at the beginning of the study. The results will be actively disseminated through peer-reviewed journals and conference presentations.Trial registration number Iranian Registry of Clinical Trials, IRCT20210217050393N1 (registered 16 May 2021).